Enhancing rice productivity by using nutrient expert - Didal, Vijay Kumar; Vidyasagar, G. E. Ch.; Kumar, R. Mahender; Brijbhooshan, Brijbhooshan (Indian Farming, 2019)
Rice productivity declines due to greater loss of nutrients from the root zone of crop. Rice productivity can be increased by minimizing nutrient losses in the environment by managing nutrient supply to the root zone within a reasonable range which realizes the biological need of crop to match nutrient requirement of crop and controls nutrient losses. To achieves this goal, use of Nutrient Expert is needed for supplying nutrients in right amount and at right time.